Modeling the new modalities of personas: How do users’ attributes influence their perceptions and use of interactive personas? - Kaate, I.; Salminen, J.; Jung, S.; Santos, J. M.; Häyhänen, E.; Xuan, T.; Azem, J.; Jansen, B. (UMAP 2024 - Adjunct Proceedings of the 32nd ACM Conference on User Modeling, Adaptation and Personalization, 2024)
We investigate the impact of user demographics (age, gender) and experience (with personas and chatbots) on users' perceptions of interactive personas. A within-subjects study was conducted with 54 participants, mostly engineers and computer scientists. Each participant used interactive personas with two interfaces: a web-based profile persona and a chat persona. The findings from regression analysis indicate that users' age and gender (as well as persona's gender) affect multiple perceptions of personas. In addition, the interface modality (profile vs. chat) has a significant impact. Findings highlight the need for designing interactive personas that appeal to diverse user bases to increase the general accessibility of interactive personas. They also support the notion that the persona interface itself regulates user perceptions even when the persona's information remains the same.